2002
DOI: 10.1002/eat.10096
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity between eating disorders and anxiety disorders: A review

Abstract: We discuss the results taking into account the methodological problems observed. We give guidelines for reviewing the results of published studies and planing future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
189
0
20

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(226 citation statements)
references
References 47 publications
12
189
0
20
Order By: Relevance
“…1 To our knowledge, this is the largest case-control study to date to explore the role of familial transmission as a potential explanatory mechanism for this association. There are two main findings.…”
Section: Main Findingsmentioning
confidence: 97%
“…1 To our knowledge, this is the largest case-control study to date to explore the role of familial transmission as a potential explanatory mechanism for this association. There are two main findings.…”
Section: Main Findingsmentioning
confidence: 97%
“…Confounding this understanding is the issue that most studies of symptoms have been done when individuals are ill with an ED. Recent studies have shown that the majority of people with AN and BN exhibit childhood perfectionism, obsessivecompulsive personality patterns, and anxiety that predate the onset of AN and BN (16,23,24). Moreover, studies done on 3 continents ( Table 2) have shown that in AN and BN individuals with a lifetime history of an anxiety disorder diagnosis, the anxiety disorder most often began in childhood before the onset of the ED (25)(26)(27)(28).…”
Section: State and Traitmentioning
confidence: 99%
“…Clinical and epidemiological studies have consistently shown that one or more anxiety disorders occur in the majority of people with AN or BN (15,16,182,183). Silberg and Bulik (184), using twins, found a unique genetic effect that influences liability to early anxiety and eating disorder symptoms.…”
Section: -Ht Da and Harm Avoidancementioning
confidence: 99%
“…7 AN is often comorbid with major depressive disorder, anxiety disorders, and multiple somatic complications. [8][9][10][11][12] Although most individuals recover, ~25% develop a chronic and relapsing course. 13 AN ranks among the ten leading causes of disability among young women 14 and has one of the highest mortality rates of any psychiatric disorder.…”
Section: Introductionmentioning
confidence: 99%